Pagan Origin of Partialist Doctrines - Pitrat, John Claudius (Salt Lake City, UT : Project Gutenberg, 2013)
"Pagan Origin of Partialist Doctrines" by John Claudius Pitrat is a historical and theological work written in the mid-19th century. The text explores the concept that various doctrines held by Partialists, particularly in the Christian faith, have their origins rooted in pagan beliefs and practices. Pitrat aims to unveil these connections through historical analysis and scriptural examination, emphasizing the impacts on modern religious understandings. The opening of the book sets the tone for an in-depth exploration of the relationship between Pagan religions and Partialist doctrines. It begins by presenting two key arguments that will be developed throughout the text: one based on scriptural analysis and the other on historical evidence. Pitrat lays out the foundations for his examination by discussing the universal worship of nature in ancient civilizations, asserting that these practices significantly shaped later religious beliefs, including concepts found in Christianity. Notably, he offers the perspective that the rituals and beliefs surrounding Pagan mysteries influenced the development of certain Christian doctrines, a theme that he promises to elaborate on in subsequent chapters in his work. (This is an automatically generated summary.)
Release date is 2013-09-03
E-text prepared by Carlos Colon, Princeton Theological Seminary Library, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (http://archive.org)
Keywords: Catholic Church -- Controversial literature; Universalism; Future punishment